Evaluasi Penataan dan Ketersediaan Koleksi pada Dinas Perpustakaan dan Kearsipan Kota Payakumbuh Berdasarkan Prinsip Menajemen Koleksi - Cinta Aura Indriani; Robby Dzakwan; Marlini Marlini (KAMPUS AKADEMIK PUBLISING, 2026)
This study was motivated by the low quality of services at the Payakumbuh City Library and Archives Office, particularly in terms of information systems, collection management, librarian competence, and the utilization of digital services. Limited access to OPAC, the absence of digital collections, manual service systems, and suboptimal external service programs indicate the need for an in-depth study of the condition of the library. This study aims to describe the actual condition of library services and identify issues that hinder the effectiveness of information services. The method used is a qualitative descriptive approach with a Waterfall system development model, using primary data through observation and secondary data through documentation and literature review. The results of the study show that library services do not yet meet modern library standards due to weak information systems, poor collection management, and inadequate human resource competencies. In conclusion, system modernization, collection development, and improvement of librarian competencies are needed to make library services more effective and relevant in the digital age.